Workability and compressive strength of concrete containing crushed cockle shell as partial fine aggregate replacement material - Abdul Basith, Abdul Halim (2014)
Various studies have been conducted on different waste products to determine the effectiveness of their use as a partial fine aggregate replacement in concrete. One such fisheries waste product is cockle shell. Cockle shell is a waste material usually dumped at landfill without treated that leads to pollution. In this research, the effect of crushed cockle shell as partial fine aggregate replacement material towards workability and compressive strength of concrete is tested. The cockle shell is crushed to obtain crushed cockle shell that suitable to be used as partial fine aggregate replacement materials. For this research, four different percentage which are 5%, 10%, 15% and 20% of cockle shell was used as partial fine aggregate replacement to produces several types of mixes. Then, specimen is prepared in form of cubes were water cured for 7, 14 and 28 days before subjected to compressive strength test. Finding shows that utilization of crushed cockle shell as partial fine aggregate replacement in concrete lower the mix workability and increase the compressive strength of concrete. At the same time, uses of cockle shell as partial fine aggregate replacement in concrete would reduce the high dependency on natural fine aggregate and offering alternatives to preserve natural sand for the use of future generation.